Narrativa de histórias pessoais: um caminho de compreensão de si mesmo à luz do pensamento de Hannah Arendt - Camasmie, Ana Tereza (2007)
The present study aims to connect the conception offered by the philosopher Hannah Arendt about the narratives of historical events with narrative of personal facts, most specifically the ones that occur during clinical psychology, rendering favourable the comprehension that man may have about himself, as the co-author of his own life. The starting-point for these thoughts concerns the way of life of the modern man, who, rooted out and heir of a world broken up with tradition, may become ill as an alternative to stand living. The growing absence of public spaces for the search of common benefit has been restricting people s suffering to the private ambit, making illness be understood as a biological or affective deficiency, thus individual. This effort in seeking in philosophy bases to the clinical work reflection is justified by the interest in understanding human existence in order to amplify the specific view of psychology about the so-called psychic sufferings. Arendt s philosophy offers resources for this consideration, most specifically about the concepts of narrative and comprehension that can be transferred to the psychotherapy extent. Understanding oneself by telling its own story is based on the idea that allows the actor of a biography to become a self-spectator as well as a narrator to the others. Nevertheless, this activity is not solitary. In order to make the self-comprehension happen it is necessary for the personal stories narrative to be dialogical, thus presenced by a witness and arisen from a truths discoverer meeting. These truths, although never absolute, always reveal the hero of his own story